2015
DOI: 10.1007/s12264-015-1538-4
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous level of TIGAR in brain is associated with vulnerability of neurons to ischemic injury

Abstract: In previous studies, we showed that TP53-induced glycolysis and apoptosis regulator (TIGAR) protects neurons against ischemic brain injury. In the present study, we investigated the developmental changes of TIGAR level in mouse brain and the correlation of TIGAR expression with the vulnerability of neurons to ischemic injury. We found that the TIGAR level was high in the embryonic stage, dropped at birth, partially recovered in the early postnatal period, and then continued to decline to a lower level in early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…G6PD is the rate-limiting enzyme of the oxPPP, which is upregulated in ischemia (Li et al, 2014), while TIGAR promotes the oxPPP at the expense of glycolysis. In line with our findings, inhibition of the oxPPP flux by silencing G6PD aggravated stroke outcome (Zhao et al, 2012), while TIGAR protects ischemic brain injury, though oxPPP flux measurements were not performed in this study (Cao et al, 2015; Li et al, 2014). Some evidence suggests a contextual role of the PPP, attributing opposing fates to NADPH.…”
Section: Discussionsupporting
confidence: 89%
“…G6PD is the rate-limiting enzyme of the oxPPP, which is upregulated in ischemia (Li et al, 2014), while TIGAR promotes the oxPPP at the expense of glycolysis. In line with our findings, inhibition of the oxPPP flux by silencing G6PD aggravated stroke outcome (Zhao et al, 2012), while TIGAR protects ischemic brain injury, though oxPPP flux measurements were not performed in this study (Cao et al, 2015; Li et al, 2014). Some evidence suggests a contextual role of the PPP, attributing opposing fates to NADPH.…”
Section: Discussionsupporting
confidence: 89%
“…TIGAR is a novel target protein involved in glucose metabolism and cerebral ischemic injury18192436. The previous study showed that TIGAR increases PPP flux and promotes the production of NADPH to remove reactive oxygen species (ROS) and to maintain cell survival24373839.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, NADPH provides the energy to shuttle isocitrate into the mitochondria to develop cellular energy homeostasis. It was previously demonstrated that exogenous NADPH could protect neurons from IRI [18]. Thus, we hypothesized that NADPH could also prevent IRI-induced kidney damage.…”
Section: Introductionmentioning
confidence: 97%